Zawahiru Ta’tsiru al Lughah al Arabiyah fi al Lughah al Hausawiyyah - Abdullah, Yaqub Alhaji ((الطموحات ) EL-THUMUHAT, 2020)
Arabic language is known as a language of Islam and the holy Quur’an.It is also a language of culture and civilization that provide the needs of its speakers at all levels and has over come the challenges of time. Arabic as a language has influenced different languages, especially the language of muslims in different part of the world. Hausa language is a clear example of such influence. Thus, this paper is an attempt to examine different aspect at which Arabic language has influence Hausa language. The inductive method was adopted in the research to draw examples and bring out similarities between the two languages. The findings of this paper therefore established that Hausa linguistic aspect that were influenced by Arabic language includes; aspect of some pronoun, formation of word, feminine gender and the usage of Arabic meter in composing Hausa poem. These affirmed the long term relationship between the two languages and confirmed the advancement of Arabic language.